FACTORS AFFECTING EXCLUSIVE BREASTFEEDING IN INFANT AT THE PUBLIC HEALTH CENTER OF ILE BURA - Kebo, Sesilia Serly; Husada, Dominicus Husada; Lestari, Pudji Lestari (Indonesian Midwifery and Health Sciences Journal, 2021)
Background: Exclusive Breastfeeding (ASI) according to WHO is the best method of feeding babies, in the period from newborns to 6 months of age without being given other additional foods. The coverage of exclusive breastfeeding in Indonesia is still around 37.3% of the 50% target. . Literature review and previous research show that the practice of exclusive breastfeeding is influenced by several factors, including maternal age, mother's occupation, mother's knowledge, family support, support from health workers and the IMD process. The purpose of this study was to analyze the factors of maternal age, occupation, mother's knowledge, family support, support from health workers and the IMD process for the process of exclusive breastfeeding to infants. Methods: An observational quantitative analytical study with a cross sectional approach. The study was conducted in the Ilebura Health Center area, from August to September 2020 with a sample of breastfeeding mothers who had babies aged 6-12 months, with total sampling. The variables in this study consisted of from the independent variables, namely maternal age, mother's occupation, mother's knowledge, family support, support from health workers, and the IMD process. The dependent variable is exclusive breastfeeding. The instrument used is a questionnaire. Data analysis using chi square test and multivariate test using logistic regression. Results: This study obtained 71 samples of breastfeeding mothers. Most of the respondents (78.9%) who gave exclusive breastfeeding were aged 25-35 years, had a good level of knowledge and did not work. All respondents in this study received support from their families and health workers, and most of the respondents (85.9) who gave exclusive breastfeeding experienced the IMD process. Bivariate test results showed the relationship between age factor (p = 0.163), occupation factor (p = 0.592), knowledge factor (p = 0.452), IMD process (p = 0.010) on exclusive breastfeeding. The results of the multivariate test showed that the most influential factor on exclusive breastfeeding was the IMD factor. Conclusion: Research shows that there is no relationship between maternal age, mother's occupation, mother's knowledge with exclusive breastfeeding, but there is a relationship between the IMD process and exclusive breastfeeding. The most dominant factor influencing exclusive breastfeeding to infants is the implementation of early initiation of breastfeeding (IMD). ). Keywords: Factors, Success, Exclusive Breastfeeding